ANALISIS IMPLEMENTASI PENETAPAN MARGIN PADA PRODUK PEMBIAYAAN KENDARAAN BERMOTOR KHUSUS ASN MELALUI AKAD MURABAHAH DALAM PERSPEKTIF FIQH MUAMALAH DI PT. BANK SUMUT SYARIAH KANTOR CABANG PEMATANG SIANTAR - Lestari, Mega Indah; Anggraini, Tuti; Nurwani, Nurwani (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This study aims to determine the implementation of setting margins on motor vehicle financing products specifically for ASN through murabaha contracts in the perspective of fiqh muamalah. This study uses a descriptive qualitative approach. Sources of data obtained through primary and secondary data, for data collection using observation, interviews and documentation. The results of this study are that in financing murabahah contracts at Bank Sumut Syariah, Pematang Siantar Branch, in implementing the margin, it is in accordance with the principle of permissibility in determining the magin. But in financing murabahah contracts for motorized vehicle products specifically for ASN, this is not in accordance with the principles of fiqh muamalah perspective, namely the principle of justice, because the determination of the profit margin is not explained in detail so that customers only know the selling price and purchase price without knowing the margin set by Bank Sumut. Sharia Branch of Pematang Siantar.